Long-term effects of human amniotic membrane in a rat model of biliary fibrosis - Sant'Anna, L.B. (Braz J Med Biol Res, 2017)
Liver fibrosis is the most common outcome of chronic liver diseases, and its progression to cirrhosis can only be effectively treated with liver transplantation. The amniotic membrane (AM) has been studied as an alternative therapy for fibrosis diseases mainly for its favorable properties, including anti-inflammatory, anti-scaring and immunomodulatory properties. It was recently demonstrated that the AM reduces the progression of biliary fibrosis to its advanced stage, cirrhosis, when applied on the liver for 6 weeks after fibrosis induction. Here, we investigated the effects of AM on rat fibrotic liver, during a prolonged period of time. Fibrosis was induced by bile duct ligation (BDL), and at the same time, a fragment of AM was applied around the liver. After 1, 3, 6, and 9 weeks, the degree of fibrosis was assessed by qualitative Knodell scoring, and by quantitative image analysis to quantify the area of collagen deposition in hepatic tissue. While fibrosis progressed rapidly in untreated BDL animals, leading to cirrhosis within 6 weeks, AM-treated livers showed confined fibrosis at the periportal area with few and thin fibrotic septa, but without cirrhosis. In addition, collagen deposition was reduced to about 36 and 55% of levels observed in BDL at 6 and 9 weeks after BDL, respectively, which shows that the longer the period of AM application, the lower the collagen deposition. These results suggested that AM applied as a patch onto the liver surface for longer periods attenuated the severity of biliary fibrosis and protected against liver degeneration caused by excessive collagen deposition.